EKSISTENSI SURAT PERSETUJUAN TOKOH ADAT DALAM PROSES PERNIKAHAN: ANALISIS PERSPEKTIF HUKUM ISLAM DI DESA SEI SALAK - Andiki Andiki; Arya Ramadhan (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study aims to analyze the existence of letters of consent from traditional leaders in the marriage process in Sei Salak Village and examine them from the perspective of Islamic law and customary law. The focus of the study includes the social and administrative functions of letters of consent from traditional leaders, the application of social and customary sanctions for violations, and their relevance to the concepts of ‘urf, maslahah, and hajjiyāt in Islamic law. This study uses a qualitative method with an empirical juridical approach and field research. Data were collected through in-depth interviews with traditional leaders, religious leaders, village officials, and the community, and supported by documentation studies and literature reviews. Data analysis was conducted using descriptive qualitative methods. The results show that letters of consent from traditional leaders function as an instrument of social control to maintain community harmony and prevent family conflict, although they do not determine the validity of marriages according to Islamic law. The customary sanctions applied are social and moral in nature, such as reprimands and social exclusion. From an Islamic legal perspective, this practice can be categorized as ‘urf sahih which contains maslahah values ​​and falls within the realm of hajjiyāt, as long as it does not conflict with sharia principles. This research emphasizes the importance of synergy between customary law and Islamic law in marriage practices.